(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to analyse the implications of Law No. 18 of 2019 concerning Pesantren (Islamic boarding schools) for Indonesia’s national resilience framework. The analysis focuses on how this legislation integrates pesantren within broader national development and resilience strategies. Study Design/Methodology/Approach: A descriptive-qualitative approach is adopted, involving document analysis of the Pesantren Law, its legislative background, and related regulatory instruments. The study is further supported by a review of relevant literature on public policy and national resilience to inform and contextualise the analysis. Findings: The findings demonstrate that pesantren have historically contributed to Indonesia’s socio-political development, particularly across the ideological, economic, educational, and socio-cultural dimensions of national resilience. The enactment of the Pesantren Law provides a formal legal foundation that strengthens the role of pesantren in promoting national unity, fostering economic empowerment, advancing educational quality, and preserving cultural heritage. Originality/Value: This study offers a distinctive perspective by linking religious education institutions with national resilience strategies through public policy analysis. Emphasising the relevance of integrating pesantren within national policy frameworks, the analysis demonstrates how such integration contributes to responding to evolving societal challenges and to reinforcing resilience across multiple dimensions.